Formulating Strategies for Increasing Business’ Competitiveness Using Performance Prism, SWOT, and SOAR - Arif, Muhammad Fuad; Lukmandono, Lukmandono (UNIPA PRESS, 2020)
RSI X is a health care institution, which now facing a growing number of competitors in its vicinity ranging from general hospital, private health clinic, and local community health centers. Not to mention many smaller health clinics owned privately by doctors. This growing number of competitors, urge RSI X to assess its current performance and to determine its strategies to be able to compete and grow its market segment. The purpose of this research is to assess RSI X current performance and to formulate appropriate business strategies in order to face the aforementioned competitors. The results of this research are performance measurement result using performance prism method and formulation of strategies using SWOT and SOAR methods. From 45 targets and 45 key performance indicators (KPI), 14 of them are good, 21 of them are moderate, and 10 of them are poor. Furthermore, from SWOT and SOAR analysis, 14 strategies are formulated.